Knowledge, skills and attitudes of older people and staff about getting up from the floor following a fall: a qualitative investigation - Swancutt, Dawn R. (BMC Geriatr, 2020)
BACKGROUND: Falls are the most common reason for ambulance callouts resulting in non-conveyance. Even in the absence of injury, only half of those who fall can get themselves up off the floor, often remaining there over an hour, increasing risk of complications. There are recognized techniques for older people to learn how to get up after a fall, but these are rarely taught. The aim of this study was to develop an understanding of attitudes of older people, carers and health professionals on getting up following a fall. METHODS: A qualitative focus group and semi-structured interviews were conducted with 28 participants, including community-dwelling older people with experience of a non-injurious fall, carers, physiotherapists, occupational therapists, paramedics and first responders. Data were transcribed and analysed systematically using the Framework approach. A stakeholder group of falls experts and service users advised during analysis. RESULTS: The data highlighted three areas contributing to an individual’s capability to get-up following a fall: the environment (physical and social); physical ability; and degree of self-efficacy (attitude and beliefs about their own ability). These factors fell within the wider context of making a decision about needing help, which included what training and knowledge each person already had to manage their fall response. Staff described how they balance their responsibilities, prioritising the individual’s immediate needs; this leaves limited time to address capability in the aforementioned three areas. Paramedics, routinely responding to falls, only receive training on getting-up techniques from within their peer-group. Therapists are aware of the skillset to breakdown the getting-up process, but, with limited time, select who to teach these techniques to. CONCLUSION: Neither therapists nor ambulance service staff routinely teach strategies on how to get up, meaning that healthcare professionals largely have a reactive role in managing falls. Interventions that address the environment, physical ability and self-efficacy could positively impact on peoples’ capability to get up following a fall. Therefore, a more proactive approach would be to teach people techniques to manage these aspects of future falls and to provide them easily accessible information.